The Effect of Customer Experience, Word of Mouth, and Price Perception on Repurchase Intention of Special Fare Train Tickets - Salma Dea Nabilla; Rizky Dermawan; Reiga Ritomiea Ariescy (Indonesian Journal of Business Analytics, 2023)
PT. KAI (Persero) is a State-Owned Enterprise (BUMN) engaged in transportation services for transporting passengers, goods, and containers. In 2019 PT. KAI (Persero) seeks to increase the number of passengers by applying for special-fare train tickets. This study aims to determine the effect of customer experience, word of mouth, and price perception on the intention to repurchase special-fare train tickets. The population in the study were customers of special fare train tickets. The sampling technique uses a non-probability sampling method with convenience sampling techniques for as many as 112 respondents. The analysis technique used in this study is (PLS) with a validity, reality, and hypothesis test. The results of this study state that customer experience and word of mouth contribute to customer repurchase intention, while price perception does not contribute to customer repurchase intention.